Aqueous Medium Preparation of Dialkyldiselenides - Manna, Tapasi; Misra, Anup Kumar (SynOpen, 2018)
One-pot, two-step reaction conditions have been developed for the preparation of dialkyl diselenides by the treatment of alkyl halides with potassium selenocyanate followed by alkaline hydrolysis of the in situ generated alkyl selenocyanate in water. The reaction is reasonably fast and the yields of the products were very good. Several functional groups present in the substrates were unaffected under the reaction conditions.
Keywords: selenium; alkyl halides; dimerization; sustainable chemistry; water